2015
DOI: 10.1038/mi.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in mucosal immune responses

Abstract: Eosinophils, multifunctional cells that contribute to both innate and adaptive immunity, are involved in the initiation, propagation and resolution of immune responses, including tissue repair. They achieve this multifunctionality by expression of a diverse set of activation receptors, including those that directly recognize pathogens and opsonized targets, and by their ability to store and release preformed cytotoxic mediators that participate in host defense, to produce a variety of de novo pleotropic mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 159 publications
2
139
0
1
Order By: Relevance
“…Under basal conditions, most eosinophils reside in the tissue where they exert key homeostatic functions (1,2,8,16). Microarray analyses revealed that lung rEos specifically expressed several genes, such as Anxa1 (46), Nedd4 (47), Runx3 (48), Serpinb1a (49), and Ldlr (50), that are involved in the maintenance of lung immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under basal conditions, most eosinophils reside in the tissue where they exert key homeostatic functions (1,2,8,16). Microarray analyses revealed that lung rEos specifically expressed several genes, such as Anxa1 (46), Nedd4 (47), Runx3 (48), Serpinb1a (49), and Ldlr (50), that are involved in the maintenance of lung immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, eosinophilopoiesis is dramatically increased as a result of Th2 cell responses associated with helminth infections or allergic diseases such as asthma (1,2,8). This increase in eosinophil production is driven by a dedicated set of cytokines, namely IL-3, IL-5, and granulocyte macrophage-CSF (GM-CSF) (1,8).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations